Level 4 PPKM Implementation Effect Of Food And Beverage Purchase Decisions On Street Vendors In Jakarta Region - Wahid Akbar Basudani (Sekolah Tinggi Agama Islam Kuningan, 2022)
Street food vendors are an integral part of the informal sector, which has made a significant contribution to urban activity in many developing countries and appears to be one of the important categories of informal economic activity. This study aims to determine whether the PPKM Level 4 policy implemented by the government affects food and beverage purchasing decisions at street vendors in the Jakarta area. This research method is quantitative research. The population in this study are people who buy food and beverages at street vendors in a number of traditional markets in the Jakarta area. The sampling technique in this research is non-probability sampling, namely incidental sampling of 100 samples. This research data is primary data. Data collection techniques with research questionnaires. Data analysis in this study is quantitative analysis by conducting tests starting with the classical assumption test research instrument consisting of normality test, heteroscedasticity test and autocorrelation test and simple linear regression analysis test. The results of this study obtained a regression coefficient of 0.255 with a significance value of 0.000 <0.05. It can be said that this research hypothesis is accepted because the PPKM Level 4 Application Variable (X) has a low positive effect on the Purchase Decision Variable (Y).